The story of America. a nation geographic picture Atlas - Copyright Collection (Library of Congress) (Washington : National SOciety, 1998)
You'll see the Pilgrims land on the wild shores of Massachusetts...celebrate the first Thanksgiving in 1621...experience what life was like at Plimonth Plantation. Then re-live the dramatic years of the American Revolution: journey along with Paul Revere on his frantic midnight ride, suffer through the bitter winter at Valley Forge with George Washington and his weary troops, and witness Thomas Jefferson as he pens the Declaration of Independence.
Copyright Collection.